Unlocking the Bioactive Potential of Pandanus conoideus Lim: A Process-Modified Approach to Double the Oil Yield and Enhance In Vitro Radical Scavenging Activity - Siti Hartinah; I Made Budi; Rini Dwiastuti (Natural Sciences Engineering and Technology Journal, 2025)
Pandanus conoideus Lim (Red Fruit), an indigenous plant of Papua, Indonesia, is a traditionally valued source of natural antioxidants. However, community-based oil extraction methods are often inefficient, leading to low yields and thermal degradation of bioactive compounds, thereby limiting the product's quality and standardization potential. This study aimed to develop and validate a process-modified extraction technique to improve both the yield and a key chemical quality marker—the in vitro antioxidant efficacy—of Red Fruit oil. Oil was extracted from Pandanus conoideus fruit using two methods: a traditional empiric method (aqueous boiling, manual pressing) and a novel modified method (steam distillation, mechanical screw pressing, centrifugation at 3500 x g, and controlled-temperature vacuum evaporation at 50°C). Oil yields were quantified on both wet and dry weight bases. The in vitro antioxidant capacity was determined using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, with the half-maximal inhibitory concentration (IC₅₀) calculated from scavenging activity at concentrations of 50, 100, 150, and 200 ppm. Commercial Vitamin E was used as a positive control. The process-modified extraction method produced a substantially greater oil yield (20.0% w/w) compared to the empiric method (10.8% w/w), representing an 85.2% increase in production efficiency. In the DPPH assay, the oil from the modified method exhibited significantly higher radical scavenging potency, with an IC₅₀ value of 63.94 ± 2.15 ppm. This was superior to the empiric method extract (IC₅₀ = 95.55 ± 3.41 ppm; p < 0.01) and the 300 IU Vitamin E standard (IC₅₀ = 75.48 ± 2.88 ppm). In conclusion, the integrated, process-modified extraction strategy successfully overcomes the critical limitations of traditional methods by improving process efficiency and preserving chemical integrity. It nearly doubles the oil yield and significantly enhances the in vitro radical scavenging activity by minimizing thermal degradation of bioactive compounds. This validated approach provides a robust framework for the standardized production of high-quality P. conoideus oil, establishing a scientific foundation for its development as a high-value, evidence-based natural product.